Pengaruh Sosial Media, Harga, dan Kualitas Produk terhadap Keputusan Pembelian di UD. Dua Putra Nganjuk - Moch. Danu Fahmi Rifai; Erwin Syahputra; Iing Sri Hardiningrum (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Business competition in the agribusiness sector demands that every entrepreneur formulates and implements effective marketing strategies to maintain consumer loyalty and increase sales. This study was conducted at UD. Dua Putra Nganjuk with the objective of analyzing the influence of social media, price, and product quality on consumers' purchasing decisions specifically for corn ose products. The research population consisted of 140 consumers, and the sample size was determined to be 84 respondents using a purposive sampling technique, targeting individuals who had made purchases and met specific criteria relevant to the study. A quantitative research approach was adopted, with data collected through a structured questionnaire. Data analysis was conducted using SPSS software, and included validity and reliability tests, classical assumption testing, multiple linear regression analysis, t-tests, F-tests, and calculation of the coefficient of determination (R²). The results showed that all three independent variables—social media, price, and product quality—had a positive and significant effect on purchasing decisions, with respective significance values of 0.006, 0.001, and 0.009. Furthermore, the F-test confirmed a simultaneous significant influence, with an F-statistic value of 534.263 and a significance level of 0.000. The coefficient of determination (R²) was found to be 0.952, indicating that 95.2% of the variation in purchasing decisions is explained by these three variables. The remaining 4.8% is attributed to other factors not examined in this study.